How long is too long? Examining waiting times and stress in human-elevator interaction - Masahiro Shiomi; Masayuki Kakio; Takahiro Miyashita (PeerJ)
Elevators have become an indispensable infrastructure in modern societies. Our use of them involves two distinct waiting periods: the waiting time (before the elevator arrives) and the transit time (riding to a destination). Reducing both is crucial for enhancing the user experience. For this purpose, researchers have focused on two approaches: such technological schemes as sophisticated elevator control algorithms for minimizing the actual waiting times, and such cognitive approaches as positioning mirrors that divert users’ attention for reducing the perceived waiting times. However, past studies failed to sufficiently examine the relationship between the actual and perceived waiting times in real elevator usage conditions; nor have they investigated how these waiting times are related to user stress. In this study we addressed these relationships by conducting an experiment that replicated real-world elevator usage scenarios and gathered both self-reported perceived waiting times and stress data from participants and objectively measured the actual waiting times by video analysis. Investigation of these data clarified the discrepancy between actual and perceived waiting times and more deeply explored how waiting times influence user stress.